2016
DOI: 10.18805/lr.v0iof.9440
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weed management on growth and yield of groundnut (Arachis hypogaea) in gangetic plains of West Bengal, India

Abstract: The field experiments were carried out at Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal, India during summer seasons of 2012 and 2013, to study the effect of weed management on growth and yield of groundnut (Arachis hypogaea L.) in gangetic plains of West Bengal. Weed biomass, weed control efficiency as well as the pods plant -1 , 100-seed weight, seed yield were significantly affected due to weed control treatments. Treatment receiving hand weeding twice recorded lowest weed biomass (3.44 g m -2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
4
3
0
Order By: Relevance
“…The probable reasons for obtaining lowest weed population under herbicides tried might be due to pre and post emergence application of herbicides resulted in better weed management during initial and later growth stages of crop due to their differed ability to control weeds as well as smothering effect of crop as lesser weed competition faced by groundnut crop. Similar results were also reported by Adhikary et al (2016) and Sahoo et al (2017).…”
Section: Other Broad-leaved Weedssupporting
confidence: 91%
“…The probable reasons for obtaining lowest weed population under herbicides tried might be due to pre and post emergence application of herbicides resulted in better weed management during initial and later growth stages of crop due to their differed ability to control weeds as well as smothering effect of crop as lesser weed competition faced by groundnut crop. Similar results were also reported by Adhikary et al (2016) and Sahoo et al (2017).…”
Section: Other Broad-leaved Weedssupporting
confidence: 91%
“…In all, pendimenthalin non-expired + one hand weeding at 6 weeks after sowing and two hand weeding at 3 and 6 WAS significantly increased the growth parameters compared to other treatments. The result obtained in this study aligned with the study of Adhikary et al (2016), who reported that application of herbicide affect the growth parameters of groundnut treated with different herbicides postand pre-emergence.…”
Section: Morphological Growth Parameterssupporting
confidence: 90%
“…The highest value of WCE (97.26 %) was obtained from weed free check treatment. Pabitra Adhikary et al(2016) earlier also reported treatment receiving hand weeding twice recorded lowest weed biomass and highest W CE (85.09 %) which was significantly higher over other treatments. Amongst herbicides, the maximum value of WCE was achieved by of Imazethapyr + Imazomox 0.10 kg /ha (80.68%) followed by Propaquizofop 0.10 kg (77.39%).…”
Section: Effect On Weed Control Efficiency and Weed Indexmentioning
confidence: 83%